NF-YB Regulates Spermatogonial Stem Cell Self-Renewal and Proliferation in the Planarian Schmidtea mediterranea - Iyer, Harini (PLoS Genet, 2016)
Gametes are the source and carrier of genetic information, essential for the propagation of all sexually reproducing organisms. Male gametes are derived from a progenitor stem cell population called spermatogonial stem cells (SSCs). SSCs give rise to male gametes through the coordination of two essential processes: self-renewal to produce more SSCs, and differentiation to produce mature sperm. Disruption of this equilibrium can lead to excessive proliferation of SSCs, causing tumorigenesis, or can result in aberrant differentiation, leading to infertility. Little is known about how SSCs achieve the fine balance between self-renewal and differentiation, which is necessary for their remarkable output and developmental potential. To understand the mechanisms of SSC maintenance, we examine the planarian homolog of Nuclear Factor Y-B (NF-YB), which is required for the maintenance of early planarian male germ cells. Here, we demonstrate that NF-YB plays a role in the self-renewal and proliferation of planarian SSCs, but not in their specification or differentiation. Furthermore, we characterize members of the NF-Y complex in Schistosoma mansoni, a parasitic flatworm related to the free-living planarian. We find that the function of NF-YB in regulating male germ cell proliferation is conserved in schistosomes. This finding is especially significant because fecundity is the cause of pathogenesis of S. mansoni. Our findings can help elucidate the complex relationship between self-renewal and differentiation of SSCs, and may also have implications for understanding and controlling schistosomiasis.